glossary of common knowledge. - Badovinak, Zdenka; Carrillo, Jesus; Piskur, Bojana; Ngcobo, Gabi; Wright, Stephen; Byrne, John; Kreuger, Anders; Aikens, Nick; Salti, Rasha; Kortun, Vasif (Moderna galerija : Ljubljana, 2018)
El-Hassan, Roza ; Ögut, Ahmet
Beyond the conventional usage of the language in contemporary art. Terms associated with referential fields, as proposed by narrators in the course of seminars, to negotiate various positions, contexts and local narratives about contemporary art.
boek